THE ROLE OF FATAYAT NU IN MAINSTREAMING RELIGIOUS MODERATION - Nadia Nurfitria (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Abstrak Fatayat Nahdataul Ulama or known as Fatayat NU is a mass women's organization that invites its administrators and members to adopt an attitude of Moderation (tawasuth). Fatayat NU's steps in mainstreaming values ​​and conceptions of religious moderation in accordance with the contents of QS. Al-Baqarah: 143 which states that the best people are moderate people, who place a middle position between the two extremes. This article was created to look at the role of Fatayat NU in mainstreaming religious moderation in Banten Province. The method used is a descriptive analysis of the role of Fatayat NU through a role theory approach. The results of the temporary study show that Fatayat NU has a very strategic role as a women's mass organization in mainstreaming religious moderation in Banten Province. As for the strategic steps he took; The Religious Moderation Workshop is a collaboration between Fatayat NU, Serang City, and the Indonesian Ministry of Religion. Activities Through regeneration. Public Dialogue Activities. Aswaja's study is guided by four attitudes, namely tasawassuth, tawazun, I'tidal, tasamuh, so that efforts to counteract radicalism in Banten can run properly. Keywords: NU Fatayat, Mainstreaming, Religious Moderation, Millennial Generation